Green Economy: Community Pottery Development Process from Kradong Volcanic Rock Powder for the Sustainable Development of Communities in Thailand - Thanate Piromgarn; Kittisak Ariyakuare; Songwut Egwutvongsa (My University, 2023)
The aim of this research is to establish a pottery production process from volcanic rock powder in Ban Kruat District, Thailand under the concept of the green economy operation by using research tools such as structured interviews as well as Exploratory Factor Analysis (EFA) and Multiple Regression Analysis. Moreover, it was found that the mixing ratios of pumice powder at 50%, local soil at 20% and kaolin at 30% with a shrinkage rate of 14%, water absorption of 1.88%, and a hardness of 304.75 kg/cm², having been fired at a temperature of 1,190 °C is considered a suitable ratio. In the same way, when transferring the production process of new pottery to the community in Ban Kruat District for production and distribution with the evaluation of consumer satisfaction, it can be summarized that there are six factors that affect consumer satisfaction: 1) Local Identity, 2) Uniqueness of the Materials, 3) Identity from Khmer Art Influence, 4) Factors in Lifestyle and Local Beliefs, 5) Functional Factors that Correspond to the Era, and 6) Factors of Current Market Conditions. Thus, these six factors have a predictive value of 61.365 (KMO =.533), and the results are as follows: F = 88.808, P = 0.000, R = 0.858, R2 = 0.736, Adj R2 = 0.728, SEE = 0.320, Durbin-Watson = 1.919. Therefore, the regression equation is defined as y ̂=-2.528+.345(X_1 )+.277(X_2 )+.287(X_3 )+.354(X_4 )+.373(X_5 )+.392(X_6 ), and it was concluded that all six factors affect consumer satisfaction towards pottery made from new types of volcanic rock powder with statistical significance at .01.

Received: 28 January 2023 / Accepted: 14 April 2023 / Published: 5 May 2023
Keywords: Sustainability and Innovation in Business